Predictions and test of multiple climate-species richness hypotheses to explain the spatial distribution of tenebrionid beetles in mountain environments - Carrara, Rodolfo (2023)
Few studies have evaluated how climate is mechanistically related to species richness in mountain environments. We used path analysis to evaluate predictions of several mechanistic hypotheses based on their hypothesized mechanism relating climate with richness of darkling beetles (Coleoptera: Tenebrionidae). We modeled the influence of spatial covariation on climatic variables and tenebrionid richness. Results showed that richness peaks at mid elevations, chiefly influenced by precipitation and temperature, both directly and indirectly through geographic range sizes. The best fitting model explains 84% of the variance of tenebrionid richness. We suggest this pattern is induced by a water-energy balance along the altitudinal gradient. At low elevations, energy availability is high but water deficit may limit species richness; in contrast, at high elevations water availability is high, but energy deficit may limit species richness. These results suggest high susceptibility of the study region to future global climate change.